2021
DOI: 10.1038/s41467-021-20897-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic sex chromosome expression in Drosophila male germ cells

Abstract: Given their copy number differences and unique modes of inheritance, the evolved gene content and expression of sex chromosomes is unusual. In many organisms the X and Y chromosomes are inactivated in spermatocytes, possibly as a defense mechanism against insertions into unpaired chromatin. In addition to current sex chromosomes, Drosophila has a small gene-poor X-chromosome relic (4th) that re-acquired autosomal status. Here we use single cell RNA-Seq on fly larvae to demonstrate that the single X and pair of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
91
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(118 citation statements)
references
References 97 publications
19
91
1
Order By: Relevance
“…We took advantage of transcriptomic profiling of various adult tissues in D. melanogaster and nine other Drosophila species to investigate tissue-specific expression of Arp53D . Confirming previous analyses, we found that all Drosophila species show significantly male-biased expression of Arp53D and almost undetectable expression in adult females ( Figure 1—figure supplement 1F , Table 2 ; Benner et al, 2019 ; Luo et al, 2020 ; Ma et al, 2018 ; Mahadevaraju et al, 2021 ; Nozawa et al, 2016 ; Rogers et al, 2014 ; Yang et al, 2018 ). In all these cases, Arp53D RNA expression is much higher in the testis than the remaining male carcass ( Figure 1—figure supplement 1F , Table 2 ).…”
Section: Resultssupporting
confidence: 90%
“…We took advantage of transcriptomic profiling of various adult tissues in D. melanogaster and nine other Drosophila species to investigate tissue-specific expression of Arp53D . Confirming previous analyses, we found that all Drosophila species show significantly male-biased expression of Arp53D and almost undetectable expression in adult females ( Figure 1—figure supplement 1F , Table 2 ; Benner et al, 2019 ; Luo et al, 2020 ; Ma et al, 2018 ; Mahadevaraju et al, 2021 ; Nozawa et al, 2016 ; Rogers et al, 2014 ; Yang et al, 2018 ). In all these cases, Arp53D RNA expression is much higher in the testis than the remaining male carcass ( Figure 1—figure supplement 1F , Table 2 ).…”
Section: Resultssupporting
confidence: 90%
“…roX1 , one of the strongest markers of MCsp1, plays a central role in dosage compensation (Mukherjee and Beermann 1965; Meller et al 1997; Hallacli et al 2012). We investigated patterns of broadly expressed genes using the methods of Mahadevaraju et al . (2021), but found no evidence of correlations between roX1 abundance and X-to-autosome expression, or variation in X-to- autosome expression among subclusters or cell types.…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 11, 2021. ; https://doi.org/10.1101/2021.06.10.447990 doi: bioRxiv preprint Rivard,Ludwig,Patel et al 20 2016; Mahadevaraju et al 2021), but continued research in this area might inform further interrogation of the forces driving atlas off of the X chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Drosophila exhibit suppression of X-linked testis-expressed genes, and transfer of such genes from the X chromosome to autosomal loci results in higher expression levels (Kemkemer et al 2014;Argyridou et al 2017;Argyridou and Parsch 2018). One of several proposed mechanisms for both the paucity of X-linked testis-expressed genes and the suppression of their expression is meiotic sex chromosome inactivation (MSCI), in which the X chromosome becomes transcriptionally silenced earlier than autosomes (Vibranovski, Lopes, et al 2009;Zhang, Vibranovski, Krinsky, et al 2010;Zhang, Vibranovski, Landback, et al 2010;Vibranovski et al 2012;Gao et al 2014;Mahadevaraju et al 2021). Thus, genes that affect meiotic or postmeiotic processes, as atlas does, could exert beneficial effects more strongly and/or for a longer period of time if they become encoded autosomally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation